Desenvolvimento de aplicações para Cidades Inteligentes baseado na plataforma InterSCity - Citron, Jhon Wislin Ribeiro (Universidade Federal de São Carlos, 2025)
Increasingly, technologies are being integrated into urban environments, such as hospital equipment, transportation systems, cameras, radars, and other devices. These technologies continuously generate data and communicate with each other, characterizing the scenarios of Smart Cities. The development of applications that assist and improve people's daily lives is essential, especially considering the population growth in urban centers. In this context, the InterSCity platform provides a development environment where data generated by different devices, such as sensors and actuators, can be simulated and used for testing and functional simulations of these applications. In this study, a case study was conducted using the InterSCity platform, demonstrating how it can be integrated into the development of applications for Smart Cities. As a result, an application focused on temperature monitoring in subway stations was developed.
Development of Smart City applications based on the InterSCity platform
Keywords: Cidades inteligentes; InterSCity; Monitoramento de temperatura; Sensores; Simulação; Smart cities; Temperature monitoring; Sensors; Simulation; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO